Reciprocal principle of molecular recognition in supramolecular chromatography - Highly selective analytical separation of cyclodextrin congeners on a silica-bonded [60]fullerene stationary phase - Bogdanski, Anja; Wistuba, Dorothee; Larsen, Kim L.; Hartnagel, Uwe; Hirsch, Andreas; Schurig, Volker (New Journal of Chemistry, 2010)
The supramolecular pair fullerene/cyclodextrin represents a new example for the concept of reciprocal molecular recognition in liquid chromatography. Through inverting their roles as selectand and selector, small-to-large-ring cyclodextrins were chromatographed on silica-bonded [60]fullerene, whereas [60]- and [70]fullerenes were previously separated on a silica-bonded β-cyclodextrin. The recognition of cyclodextrins of intermediate ring size on silica-bonded [60]fullerene is highly selective. Thus, CD8, CD9 and CD10 are separated both from lower (CD6 and CD7) and higher (CD11-CD25) congeners with a remarkable and unprecedented retention window. By using the retention-increment method, employing a reactor column (with selector) and a reference column (without selector), apparent relative complexation constants K of CD6-CD12 and [60]fullerene were determined by supramolecular liquid chromatography. The historical development of the reciprocal principle of molecular recognition in chromatography is reported in the introduction. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.